Identification of Natural Infections in Sheep/Goats with HoBi‐like Pestiviruses in China. Issue 5 (31st July 2016) - Shi, H.; Kan, Y.; Yao, L.; Leng, C.; Tang, Q.; Ji, J.; Sun, S.
Summary: The natural infections of HoBi‐like pestiviruses in cattle have been reported in South America, Europe and Asia. In China, although the detections of HoBi‐like pestivirus have been reported, the epidemiological investigation was limited. From January 2014 to October 2015, several flocks of sheep/goats in Henan province in central China suffered respiratory diseases which were recovered slowly after antibiotics treatment. To test whether it is the HoBi‐like pestivirus caused this symptom, 49 serum samples and 22 nasal swabs were then collected for analysis by serology and RT‐PCR. Serological result revealed that prevalence of pestivirus in small ruminants was 12.2% (6/49) in central China. Sequence analysis of partial 5′‐UTR nucleotides of pestivirus‐positive samples suggested that HoBi‐like pestivirus might have circulated in sheep/goats of China for a period and have evolved into new genotype clusters. It is apparent that the study provides the molecular evidence of natural infections in goat/sheep species with HoBi‐like pestiviruses in China.